A common polymorphism decreases LRP1 mRNA stability and is associated with increased plasma factor VIII levels - Lee, Jiann-Der; Hsiao, Kuang-Ming; Chang, Pey-Jium; Chen, Chih-Cheng; Kuo, Ya-Wen; Huang, Yen-Chu; Hsu, Huan-Lin; Lin, Ya-Hui; Wu, Chih-Ying; Huang, Ying-Chih; Lee, Meng; Hsu, Chia-Yu; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2017)
The low-density lipoprotein receptor-related protein 1 (LRP1) gene is associated with increased levels of plasma factor VIII (FVIII). We aimed to explore eight functional genetic LRP1 variants for their potential roles in regulating FVIII levels and acute ischemic stroke (AIS). This genetic association study enrolled 192 patients with AIS and 134 controls. There were no significant differences in the genetic frequency of the eight functional single-nucleotide polymorphisms (SNPs) between the control and AIS groups. However, while analyzing the association between the eight SNPs and plasma FVIII levels, subjects with T/T genotype of rs1800137 (vs. CC+CT) were found to be associated with higher FVIII levels (23.5IU/dL; 95% confidence interval, 7.4–39.5IU/dL; P=0.0044) after adjusting for age, gender, estimated glomerular filtration rate, O blood type, inflammatory state, and body mass index. An analysis of the mRNA stability and abundance was designed and performed using minigene system transfected into HepG2 cells to assess the possible differences in mRNA stabilities between rs1800137 CC (rs1800137C) and TT (rs1800137T) genotypes. Site-directed mutagenesis revealed that rs1800137T accounts for the observed decrease in mRNA stability. The SNP rs1800137, located in exon 8, has been identified as an exon-splicing enhancer in silico. However, alternative splicing of LRP1 without inclusion of exon 8 was not identified. In transfected HepG2 cells, cycloheximide slowed down the degradation of the rs1800137T-containing minigene. These results demonstrate that synonymous SNP rs1800137 can lead to increased plasma FVIII levels due to decreased mRNA stability via translation-dependent mRNA degradation associated with codon optimality. [Display omitted] •LRP1 has been shown to interact with factor VIII and mediate its cellular uptake into the lysosomal degradation pathway.•LRP1 rs1800137 is associated with significant changes in LRP1 mRNA stability due to different codon optimality.•LRP1 rs1800137 is associated with significant changes in plasma factor VIII levels by modulating the expression of LRP1 mRNA.